Evaluation of Front Line Demonstrations on Summer Moong (Vigna radiata) in Sangrur district of Punjab - Kaur, Prabhjot; Kumar, Pankaj (Indian Journal of Extension Education, 2020)
The study was conducted with an objective of enhancing farmersâ€™ income through crop intensification. A totalÂ of 175 front line demonstrations were conducted on summer moong (Vigna radiata) var. SML 668, during year 2017 and 2018 and SML 832 during year 2019 in two adopted villages of Sangrur district under Farmer FIRST Project. During the year 2017, a yield of 10.84 q/ha and 9.38 q/ha was obtained in FLD plots and local checks respectively. During 2018 and 2019, average yield of 10.25 q/ha and 10.30 q/ha was obtained in FLD plots asÂ compared to 9.30 q/ha and 9.02 q/ha respectively in local check plots. Cost of cultivation of the summer moong at demonstrated field was Rs. 17918.57/ha whereas it was 16687.85/ha in case of farmersâ€™ fields during 2017 and net returns of the demonstrated field and local check were Rs. 38720.43/ha and Rs. 32322.64/ha respectively. The B:C ratio of the demonstrated and local check were 3.16 and 2.94 respectively. In 2018 BC ratio of 2.96 and 2.71Â was obtained in FLDs and check plots and during 2019 BC ratio of 2.94 and 2.44 was obtained in FLDs and check plots respectively. Farmers were unaware about the appropriate time of application and adequate dose ofÂ the pesticides.